Meningkatkan Kemampuan Berbahasa Anak Melalui Metode Karyawisata di TK Balitka Manado - Djailan Mansur (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research was conducted with the problem of whether the field trip method can improve children's language skills. Children's language skills are important because with language (children aged 4-5 years) children can communicate with friends or people around them. Language is the main form of conveying messages, thoughts, and being able to relate to other people. Language skills are needed in developing aspects of language to children, because children can communicate or relate to other people. Children understand many things better and can increase their vocabulary more. Field trips are one of the learning methods in kindergarten that are carried out outside of school, observing the world according to the realities that exist directly, for example humans, animals and plants, the surrounding nature and other objects. Children can directly observe the conditions that exist in the natural surroundings so that with these conditions children can understand and give an impression of the results of their observations through the five senses of what is seen, heard, and touched. Using this field trip method helps children increase the vocabulary of what they see, by directly and making children interesting and happy with what they observe. Thus it will be easy to develop children's language. The benefits of this field trip method are for children to get to know and learn something real. With field trips, children also learn to observe and do other activities. The use of this field trip method makes children interesting and fun and is liked by many children. School education can take advantage of the environment and nature as a tourist attraction. Thus it will be easier to develop children's language skills through good communication and the use of correct language. The strategy used by the teacher is to help children to be able to speak well. With field trips, children also learn to observe and do other activities, such as role playing, matching pictures with word stories and so on.